Association of pancreatitis with risk of diabetes: analysis of real-world data - Ba, Djibril M.; Chinchilli, Vernon M.; Cozzi, Anna M.; Bradley, David P.; Pichardo-Lowden, Ariana R. (Frontiers in Clinical Diabetes and Healthcare, 2024)
Introduction: Diabetes is a major cause of disease burden with considerable public health significance. While the pancreas plays a significant role in glucose homeostasis, the association between pancreatitis and new onset diabetes is not well understood.The purpose of this study was to examine that association using large real-world data.: Utilizing the IBM® MarketScan® commercial claims database from 2016 to 2019, pancreatitis and diabetes regardless of diagnostic category, were identified using International Classification of Diseases, Tenth Revision [ICD-10] codes.We then performed descriptive analyses characterizing non-pancreatitis (NP), acute pancreatitis (AP), and chronic pancreatitis (CP) cohort subjects. Stratified Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) of diabetes across the three clinical categories.In total, 310,962 individuals were included in the analysis. During 503,274 person-years of follow-up, we identified 15,951 incident diabetes cases. While men and women had higher incidence rates of CP and AP-related diabetes, the rates were significantly greater in men and highest among individuals with CP (91.6 per 1000 persons-years (PY)) followed by AP (75.9 per 1000-PY) as compared to those with NP (27.8 per 1000-PY). After adjustment for diabetes risk factors, relative to the NP group, the HR for future diabetes was 2.59 (95% CI: 2.45-2.74) (P<0.001) for the CP group, and 2.39 (95% CI: 2.30-2.48) (P<0.001) for the AP group.Pancreatitis was associated with a high risk of diabetes independent of demographic, lifestyle, and comorbid conditions.